Why (Not) Engage: Perceived Limits of Civic Agency and Barriers to Participation in Armenia - Manusyan, Sona; Poghosyan, Ani; Gasparyan, Ani; Khachatryan, Narine (Bulletin of Yerevan University E: Philosophy, Psychology, 2026)
The aim of the article is to discuss, from a socio-psychological perspective, the perceived limits of influencing developments in the country and the barriers to civic engagement among youth in post-revolutionary and post-war Armenia. Both theory and social practice suggest that perceived opportunities of participating in social change and influencing social reality have practical implications for actual (non)participation, which, in turn, feeds back to the construction of that reality. Given the civic participation decline within the complex conditions of post-war uncertainty, the study of perceived engagement barriers and limits is key to identifying and fostering meaningful forms of collective agency and civic participation. The analysis is based on focus group interviews conducted in Yerevan and four regions of Armenia in 2024. The findings reveal structural (supra-individual), group(community)-level, and individual-level factors through which participants interpret their own (non)engagement.
Keywords: civic participation; (dis)engagement; perceived limits/barriers; agency; collective efficacy